Design and Optimization of Self Nano-Emulsifying Drug Delivery System Containing a New Anti-inflamatory Agent Pentagamavunon-0 - Ika Yuni Astuti; Marchaban Marchaban; Ronny Martien; Agung Endro Nugroho (Indonesian Journal of Chemistry, 2017)
Pentagamavunon-0 is a potent anti-inflammatory drug. The oral bioavailability of PGV-0 is very low due to its low solubility in water. The aim of this study is to design and optimize SNEDDS formulation to improve dissolution of PGV-0 by Simplex Lattice Design. The independent variables were the amounts of oleic acid (X1), Tween 20 and labrasol (X2), and PEG 400 (X3). The dependent variables were droplet size (Y1), the concentration of PGV-0 dissolved in the 45th min (C45) (Y2) and solubility of PGV-0 (Y3) fitted to a quadratic model. The equation, contour plots, and overlay plot were constructed to determine the optimum formulation and to understand the responses to various combinations of components. The optimum formulation of SNEDDS consists of 18.6% oleic acid, 51.4% Tween 20:labrasol 1:1 and 30% PEG 400. The C45 of the optimum formulation is 82.20%, significantly higher than unmodified PGV-0. The droplet size is 75.45 nm and solubility of PGV-0 is 31.80 mg/mL. The predicted values are not significantly different with the experimental values. The amount of oleic acid is the most influential factor to increase droplet size and decrease the C45. The mostinfluential factor to increased C45 is the amount of PEG 400.